2013
DOI: 10.1161/strokeaha.113.003058
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for Acute Ischemic Stroke in Patients With Cancer

Abstract: Background and Purpose— The safety of thrombolysis for acute stroke in patients with cancer is not well established. Our aim is to study the outcomes after thrombolysis in patients with stroke with cancer. Methods— Patients with acute ischemic stroke who received thrombolysis were identified from the 2009 and 2010 Nationwide Inpatient Sample. Patients with cancer-associated strokes and noncancer strokes were compared based on demographics, comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 6 publications
(2 reference statements)
4
64
3
1
Order By: Relevance
“…Oberndorfer et al 12 suggested that cancer may increase the risk of hemorrhagic complications. However, our experience together with recent observations of Murthy et al 24 show that alteplase can be used safely and successfully in this group of patients, irrespective of the type of cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Oberndorfer et al 12 suggested that cancer may increase the risk of hemorrhagic complications. However, our experience together with recent observations of Murthy et al 24 show that alteplase can be used safely and successfully in this group of patients, irrespective of the type of cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Patients with cancer were divided into three categories based on the National Comprehensive Cancer Network classification: solid tumors without metastases (ICD-9-CM 140.xx- 190.xx, 193.xx-195.xx, 209.00–209.30), hematologic tumors without metastases (200.xx-208.xx, 238.7x), and metastatic solid or hematologic tumors (196.xx-198.xx, 209.7x). (12) The ICD-9 codes for individual cancers have been used in prior NIS studies(13, 14), and can be obtained using the Clinical Classification Software provided by the Healthcare Cost and Utilization Project. (15)…”
Section: Methodsmentioning
confidence: 99%
“…Patients with systemic malignancies and brain tumors are generally perceived to have a higher risk of intracerebral hemorrhage (ICH) and worse outcomes, and are therefore usually excluded from intravenous thrombolysis. Recent retrospective observational studies have suggested that thrombolysis outcomes may be favorable in patients with systemic malignancies, with no difference in ICH rates among liquid, solid or metastatic tumors [7,8]. On the other hand, literature on outcome of stroke thrombolysis in patients with brain tumors is limited to case reports with possible publication bias for favorable outcomes [9].…”
Section: Introductionmentioning
confidence: 99%